Upacara Adat Baritan: Bentuk Akulturasi Budaya Jawa dan Ajaran Islam di Desa Buluagung, Kecamatan Siliragung, Kabupaten Banyuwangi - Styawan, Dirga Candra (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyse the meanings contained in the Baritan traditional ceremony held in Buluagung Village, Siliragung District, Banyuwangi Regency, East Java. The traditional Baritan ceremony is held in the afternoon before the night of the Javanese New Year or commonly called ‘malem 1 suro’ at each village intersection. Based on the results of the research, the Baritan traditional ceremony is a form of local wisdom that contains the value of Javanese cultural acculturation and Islamic teachings. This traditional ceremony is held as a form of gratitude to God Almighty and prayers for safety from disasters. This research uses data collection techniques through observation and literature study.